Surviving Acute Organ Failure: Cell Polyploidization and Progenitor Proliferation. Issue 5 (May 2019) - Lazzeri, Elena; Angelotti, Maria Lucia; Conte, Carolina; Anders, Hans-Joachim; Romagnani, Paola
Abstract : In acute organ failure, rapid compensation of function loss assures survival. Dedifferentiation and/or proliferation of surviving parenchymal cells could imply a transient (and potentially fatal) impairment of residual functional performance. However, evolution has selected two flexible life-saving mechanisms acting synergistically on organ function recovery. Sustaining residual performance is possible when the remnant differentiated parenchymal cells avoid cell division, but increase function by undergoing hypertrophy via endoreplication, leading to polyploid cells. In addition, tissue progenitors, representing a subset of less-differentiated and/or self-renewing parenchymal cells completing cytokinesis, proliferate and differentiate to regenerate lost parenchymal cells. Here, we review the evolving evidence on polyploidization and progenitor-driven regeneration in acute liver, heart, and kidney failure with evolutionary advantages and trade-offs in organ repair. Highlights: Acute injuries of heart, liver, and kidney, which present clinically as diverse syndromes, share numerous pathophysiological mechanisms. Survival of dedifferentiated parenchymal cells and/or widespread proliferation is often spoken of as a potential mechanism of repair for acute injuries. Recently, two types of responses after acute organ failure have appeared to be shared in the liver, heart, and kidney: (i) surviving differentiated parenchymal cells undergo cell hypertrophy via polyploidization; and (ii) a population of progenitors, mostly identified as resident, more immature diploid parenchymal cells, self-renew and differentiate to replace lost cells. In order to guarantee uninterrupted life-saving functional performance after acute failure, essential organs such as the heart, liver, and kidney avoid widespread proliferation that would be largely counterproductive because it implies a transient loss of the specialized cellular functions. Therefore, these organs require polyploidization in order to sustain organ function. In the liver, polyploidization after acute failure is the predominant but not the only response. Indeed, the increase in hepatocyte ploidy precedes the proliferation of diploid hepatocyte progenitors. Polyploidization of hepatocytes drives functional recovery, increasing the metabolic function in output, whereas, hepatocyte progenitor proliferation drives the restoration of liver mass by generating new hepatocytes. In the heart, it is still debated whether newly generated cardiomyocytes originate from pre-existing cardiomyocytes that retain their proliferative capacity throughout adulthood or from a population of cardiomyocyte progenitors. Cardiomyocyte progenitors can proliferate following injury but this ability declines with aging in the mammalian heart. In the mammalian neonate the heart exhibits a high regenerative capacity due to the presence of diploid cardiomyocyte progenitors. In the mammalian adult heart, the regenerative capacity is almost lost and an increase of polyploidy results in scars in the long run. In the kidney, polyploidization in response to injury, was known solely in podocytes. However, recent findings have demonstrated that injured tubules respond to acute tubular necrosis through two main mechanisms: (i) endoreplication-mediated hypertrophy of remnant tubular epithelial cells, aiming to sustain renal function despite significant epithelial cell necrosis; and (ii) survival and proliferation of tubular progenitors, aiming to replace tubular cell loss. Since polyploid cells mostly maintain a single nucleus, their identification has become feasible thanks to an advanced technology of cell cycle phase live imaging combined with DNA quantitation. Benefits of polyploidization and proliferation associate with distinct trade-offs, including fibrosis, senescence, and cancer. Evolution has favored the coexistence of both mechanisms in the same organs, ensuring a correct self-balance of these responses.